2016
DOI: 10.1038/bmt.2016.260
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of general discomfort, limitations in activities of daily living and intention of a second donation in unrelated hematopoietic stem cell donation

Abstract: We performed a retrospective study of 1868 consecutive unrelated donors to predict the risk factors related to general discomfort, limitations in activities of daily living (ADLs) and intention of a second donation in hematopoietic stem cell (HSC) donation. General discomfort and limitations in ADLs were assessed by numerical measurement (scores of 0-10) and donor's intention of a second donation by yes or no reply. The post-donation questionnaires were completed within 48 h after HSC collection and at 1 week,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…All HSC donors who participated in this study responded that they experienced at least one or more forms of physical discomfort during the HSCD process. The types of physical discomfort experienced by the participants consisted, in decreasing order of frequency, of myalgia, bone pain, fatigue, and headache, corroborating a previous study [8]. Although G-CSF has mild side-effects in general, donors may develop various symptoms leading to physical discomfort which can also cause changes to some test results [16].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…All HSC donors who participated in this study responded that they experienced at least one or more forms of physical discomfort during the HSCD process. The types of physical discomfort experienced by the participants consisted, in decreasing order of frequency, of myalgia, bone pain, fatigue, and headache, corroborating a previous study [8]. Although G-CSF has mild side-effects in general, donors may develop various symptoms leading to physical discomfort which can also cause changes to some test results [16].…”
Section: Discussionsupporting
confidence: 84%
“…A study assessing the general discomfort and degree of restriction to daily life experienced by HSC donors [8] suggested that being female and going through bone marrow and PBSC collection via central line are predictors of general discomfort. One point to note is that being pessimistic about donating a second time or deciding not to do so were included as predictors of general discomfort, indicating that experience of the donation process can affect willingness to donate in future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Driven in part by registry regulations, the preponderance of information is on volunteer unrelated donors describing periprocedure and short-term events. Of interest, as in the current study, these studies previously identify female gender as a risk factor for increased toxicity [3,4].…”
mentioning
confidence: 78%